Mango compost extract for enhancing growth and yield of momordica charantia / F.Y. Tsan ... [et al.]. - Tsan, Fui Ying; Ngilah, E.I.; Gundadon, H.; Choo, C.Y.; Mohd Roseli, Ahmad Nazarudin (2018)
Mango as a climacteric fruit is known to have increased auxins with concomitant increased ethylene and carbon dioxide production during ripening. Such hormonal properties alongside many other nutritional benefits prepared in the form of compost extract were tested for enhancing production of medicinal bitter gourd of Momordica charantia. This cucurbit was planted on field beds at 0.8 x 0.5 m followed by application of compost extract prepared with anaerobic decomposition of rotting mango fruits, fish wastes of gills and internal organs and brown sugar at different ratios in plastic containers. The results obtained showed that mango:fish wastes:sugar compost extract of 2:1:1 applied to soil around the root collar at 10 ml at fortnight intervals allowed the plants to gain the highest mean number of fruits per plant of 18.3, mean individual fruit weight of 25.95 g or mean yield of 11.80 tonnes per hectare. Mango compost extract is, hence, beneficial in organic production of this medicinal bitter gourd.